Plain weave glass-fibre composite joints With Co2 Laser ablation architected treatments - Soares, Luiza; Ferreira, Thayane; Campuzano, Alberto; Grasso, Marzio; Camanho, Pedro; Scarpa, Fabrizio; Panzera, Tulio (Sage, 2026)
Glass Fibre Reinforced Polymers (GFRP) are particularly notable for their cost-effectiveness and versatility, finding widespread applications across aerospace, automotive, marine, medical, and sport industries. While the use of adhesive joints in GFRPs is widespread, laser ablation as a surface treatment prior to joining remains relatively unexplored. This study investigates the effects of laser ablation parameters, specifically scanning speed and power, on the surface characteristics of plain weave GFRP. Single-lap shear tests compare untreated and laser-treated joints with different architected groove spacings. Higher scanning speeds, particularly with 0.5 mm spacing, reduce fibre damage, whereas higher laser power levels increase it. Laser treatment improves shear strength by 19%, due to improved mechanical interlocking between the adhesive and the treated surface. When fibres exposure is carefully controlled, the strength of the joints improves by up to 60%. However, excessive resin degradation lowers performance; this indicates that balancing surface roughness and preserving surface integrity is critical to optimise laser ablation treatments.
Keywords: Bonded joints; glass fibre reinforced polymer; laser ablation; single lap testing; surface treatment; 40 Engineering; 4016 Materials Engineering; 4001 Aerospace Engineering; Bonded joints; glass fibre reinforced polymer; laser ablation; single lap testing; surface treatment